Easter Egg as a Means of Spiritual Education - Maksymovych, Olha; Poiasyk, Oksana (Pedagogical Discourse, 2012)
The problem of spiritual revival of the Ukrainian society, in particular by means of the painted Easter egg is revealed in the article.